2013
DOI: 10.1007/s11606-012-2249-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement Drug Use Among Future Physicians: Findings from a Multi-Institutional Census of Medical Students

Abstract: Use of psychostimulants, including use without a prescription, is common among medical students. Further study of the side effects, medical implications, and use during post-graduate medical training and medical practice is needed to inform evidence-based policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
3
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 26 publications
6
78
3
13
Order By: Relevance
“…Using the randomized response technique (RRT) in a paper-and-pencil survey among 2 569 students in Germany, the estimated 12-month prevalence of cognitive-enhancing drug use (stimulant drugs, caff eine tablets, cocaine, methylphenidate and mephedrone) was found to be 20 % [ 10 ] . The lifetime prevalence for the non-medical usage of psychostimulants, such as methylphenidate or amphetamine salts was found to be 18 % in an online survey of 2 732 medical students in the USA [ 11 ] . Future representative studies in Switzerland will reveal if our data concerning the number of CEusers are biased.…”
mentioning
confidence: 99%
“…Using the randomized response technique (RRT) in a paper-and-pencil survey among 2 569 students in Germany, the estimated 12-month prevalence of cognitive-enhancing drug use (stimulant drugs, caff eine tablets, cocaine, methylphenidate and mephedrone) was found to be 20 % [ 10 ] . The lifetime prevalence for the non-medical usage of psychostimulants, such as methylphenidate or amphetamine salts was found to be 18 % in an online survey of 2 732 medical students in the USA [ 11 ] . Future representative studies in Switzerland will reveal if our data concerning the number of CEusers are biased.…”
mentioning
confidence: 99%
“…Descriptions of formal wellness curricula have been published and should be studied for their effectiveness. 10 Too much is at stake for our patients and our learners to let warning signals, such as those demonstrated by the study from Emanuel and colleagues, 6 go unheeded.…”
mentioning
confidence: 99%
“…The danger of addiction to Ritalin® was regarded as lower than when taking illegal drugs [48]. Due to their own experience with misuse, 16% of medical students would prescribe stimulants more thoughtlessly in future [36].…”
Section: Consequences Of Methylphenidate Misusementioning
confidence: 99%
“…13) mentioned the fact that parents of children with ADHD diagnosis do not give their children methylphenidate over the weekend but sell this "saved" drug at the university. To date studies about MPH misuse have indicated an illegal market at schools and universities; however, only university students and school children giving away or selling methylphenidate have been mentioned in these studies [16] [24] [36] [37] [46] [56]. The fact that parents knowingly deprive their children of the drug-which is funded by the health insurance schemes-was not mentioned in any publication.…”
Section: Inquiries With Regard To Non-indicated Methylphenidate Prescmentioning
confidence: 99%
See 1 more Smart Citation